Семантическая деривация в истории русского языка - Николаев, Геннадий (Studia Rossica Posnaniensia, 2014)
The article is devoted to the problem of semantic word-formation in the history of the Russian language. Considering the way in which secondary language signs are formed, it is possible to speak about the semantic derivation with reference to the final period of semantic syncretism in the history of Russian (end of the 14th century).